Direct ex vivo analysis of hepatitis B virus-specific CD8(+) T cells associated with the control of infection. - Maini, M; Boni, C; Ogg, G; King, A; Reignat, S; Lee, C; Larrubia, JR; Webster, G; Mcmichael, A; Ferrari, C; Williams, R; Vergani, D; et al. (1999)
BACKGROUND and AIMS: Cytotoxic T cells have been suggested to be responsible for lysis of hepatitis B virus (HBV)-infected hepatocytes and control of virus infection. The frequency, kinetics, phenotype, and capacity for clonal expansion of circulating HBV-specific CD8 cells were analyzed directly in patients with acute HBV infection to clarify their pathogenetic role. METHODS: Three HLA-A2 peptide tetramers able to visualize HBV core, envelope, and polymerase epitope-specific cytotoxic T lymphocytes were synthesized and used for flow cytometric analysis of antigen-specific populations. RESULTS: Tetramer-positive cells specific for the core 18-27 epitope were found at a higher frequency than those specific for polymerase 575-583 and envelope 335-343 epitopes in most patients with acute HBV. The number of HBV-specific CD8 cells was highest during the clinically acute stage of infection and decreased after recovery. These cells expressed an activated phenotype and had an impaired capacity to expand in vitro and to display cytolytic activity in response to peptide stimulation. Recovery of these functions was observed when the frequency of specific CD8 cells decreased, coincident with a progressive decrease in their expression of activation markers. CONCLUSIONS: This study provides the first ex vivo evidence that the highest frequency of circulating HBV-specific CD8 cells coincides with the clinically acute phase of hepatitis B. These cells exhibit an activated phenotype with limited further proliferative capacity that is restored during recovery.